High protein pastures in spring - effects on body composition in reindeer - Eilertsen, Svein M.; Schjelderup, Ivar; Dryden, Gordon McL.; Mathiesen, Svein D. (Rangifer, 2001)
In 1996 and 1997 three groups of reindeer from different nutritional origin and condition, (poor condition groups n=15 in 1996, n=7 in 1997, good condition group n=10 in 1997), were used to investigate effects of high protein pastures on body condition for 3.5 weeks in spring. Mean body mass (BM) of reindeer in the poor condition groups increased by 10% both in 1996 (P<0.05) and in 1997 (P<0.05), while there were no significant (NS) changes in BM of reindeer in the good condition group in 1997. The mean carcass weight as % of BM increased from 48 to 51% in both the poor condition group in 1996 (NS), and in the good condition group in 1997 (P<0.05). The reticulo-rumen wet weight in the poor condition group in 1996, tended to decrease from 15.1 to 11.9% of BM, while the reticulo-rumen wet weight decreased from 14.2 to 13.0% of BM (P<0.05) in the good condition group in 1997. Mean kidney fat decreased by 51% in the poor condition group in 1996 and by 40% in the good condition group in 1997 (P<0.05). Likewise, marrow fat decreased by 50% (P<0.05) in the good condition group in 1997. In both animal groups muscle mass and carcass mass increased in the reindeer, while fat deposits decreased when eating as much as 131 g dry matter/kg0.75 on a high protein spring pasture containing as much as 30% crude protein of dry matter (DM). Much of the energy available from forage plants eaten and the body fat deposits therefore seem to support body protein growth in spring.